Design and experimental study of the end-effector for broccoli harvesting - Zhao, Xiong; Xu, Gangji; Zhang, Pengfei; Yu, Gaohong; Xu, Yadan (International Journal of Agricultural and Biological Engineering, 2024)
The end-effector is an important part of the broccoli harvesting robot. Aiming at the physical characteristics of a large broccoli head and thick stem, a spherical cutting tool broccoli harvesting end-effector was designed in this study. First, the physical characteristics of broccoli were tested, and physical parameters such as the broccoli head diameter and stem diameter of broccoli were measured. The maximum cutting force of broccoli stems under different cutting angles was tested. Second, according to the physical characteristics and harvesting process of broccoli, the end-effector was designed, and the mathematical model of kinematics and dynamics was established. Based on the results of dynamic analysis, the end-effector rod was optimized, and the unilateral width of the slider was 40 mm, the length of the connecting rod was 120 mm, and the length of the crank was 42 mm. The mechanism needed an external driving force of 140.54 N to cut the broccoli stem. Therefore, a 32 mm cylinder with a load rate of 50% was selected as the power source. Finally, the feasibility of the broccoli harvesting end-effector was verified by the harvesting test. Experiments showed that the overall harvesting success rate of the end-effector is 93.3%, and the smoothness rate of the stem section is 83.3%. The harvesting performance of the broccoli end-effector was verified. This lays a foundation for agricultural robots to harvest broccoli. Keywords: harvesting robot, broccoli, end-effector, dynamic analysis, mechanism optimization DOI: 10.25165/j.ijabe.20241701.8110 Citation: Zhao X, Xu G J, Zhang P F, Yu G H, Xu Y D. Design and experimental study of the end-effector for broccoli harvesting. Int J Agric & Biol Eng, 2024; 17(1): 137-144.